Interpretation and significance of the definition of anti-Mullerian hormone in the practice of juvenile gynaecologist - Zaira K. Kumykova; Elena V. Uvarova; Zalina K. Batyrova (IP Berlin A.V., 2021)
The article presents an overview of the physiological role of anti-Mullerian hormone (AMH) during persons lifetime, the fluctuations of its values from birth to the reproductive period in women, the significance of its determination in the diagnosis and prognosis of treatment outcomes for many gynecological diseases. AMH is produced mainly by preantral and early antral follicles and decreases during the final maturation and luteinization. AMH plays a potential role in preserving the ovarian reserve by performing dual actions. AMH inhibits the initial recruitment of follicles, preventing the influence of stimulating growth factors for recruitment (KIT-ligand, the main fibroblast growth factor). From the moment of puberty, AMH reduces the sensitivity of primary follicles to the follicle-stimulating hormone, reducing the likelihood of their cyclic recruitment. The systematic review data presented the characteristics of the ovarian reserve in a healthy female population aged 0 to 19 years. At birth, very low AMH values were noted with an increase in its level in the first 3 months of life, followed by a monthly increase of 31%. A significant increase in AMH secretion was revealed by the beginning of puberty, then most authors noted a constant level of serum AMH in the adolescent period. The level of AMH in the blood serum decreases with an increase in chronological age by 68% annually and varies during the menstrual cycle. AMH is an important diagnostic tool in pediatric practice when differentiating various causes of puberty disorders, virilization and menstrual cycle disorders in girls.